A MEMS resonant accelerometer with sensitivity enhancement and adjustment mechanisms. (16th October 2017) - Ding, Hong; Wang, Wen; Ju, Bing-Feng; Xie, Jin
Abstract: This paper proposes a resonant accelerometer with sensitivity enhancement and adjustment mechanisms based on microelectromechanical systems (MEMS). Different from conventional resonant accelerometers with sensitivity only enhanced by microleverage mechanisms, the proposed accelerometer utilizes a fishbone-shaped resonator as sensing element to enhance and adjust sensitivity. The fishbone-shaped resonator can realize the mode selection and frequency-tuning function according to the configuration of sensing and driving electrodes, so then different modes yields different sensitivities. Experimental results demonstrate that the mean differential sensitivities span from 12.44–61.00 Hz g −1 (Mode 1: 12.44 Hz g −1 ; Mode 2: 36.94 Hz g −1 ; Mode 3: 61.00 Hz g −1 ) and the average resonant frequencies are 116.47 kHz, 299.87 kHz and 548.35 kHz, respectively. Moreover, the preliminary tilt experiment verifies that this prototype has potential usage in tilt measurement.